Faktor Peminjaman Tidak Sah (Unauthorized Borrowing) Bahan Pustaka Oleh Pemustaka di Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang - Tustiver, Adrimon; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This study aimed to describe: (1) the factors that cause unauthorized borrowing of library materials by users in the Kantor Arsip, Perpustakaan dan Dokumentasi Kota Padang (2) prevention efforts being made to overcome the unauthorized borrowing of library materials by users in the Kantor Arsip, Perpustakaan dan Dokumentasi Kota Padang. The data were collected by means of observation and interviews with librarians. Analyzing data descriptively. First, the unauthorized borrowing (unauthorized borrowing) library materials by users in the Kantor Arsip, Perpustakaan dan Dokumentasi Kota Padang include ease of access that frees users to misuse the collection, the collection of interest such as fiction and novels are widely abused, age of users is still unstable often destructive acts, opening hours are too long operations, the absence of photocopy services, lack of safety, design of buildings and the library that are not optimal in meeting such requirements and convenience of the location, the lack of specialized training for librarians in crime prevention and regulatory library. Second, prevention efforts being made to overcome the unauthorized borrowing of library materials by users, by improving services, facilities, security systems such as the implementation of electronic security systems such as alarm sensors and CCTV. Conduct training for librarians and increase user awareness socialization to keep collections through user education. Keywords: unauthorized borrowing; library materials